Pattern of dyslipidaemia in human immunodeficiency virus infected patients- a study from rural tertiary care hospital in central India - Wafai, Nisar A.; Zafar, Khwaja Saifullah; Kumar, Manoj; Singh, Prem S.; Yadav, Sudhir K. (International Journal of Research in Medical Sciences, 2016)
Background: HIV/AIDS is a major health problem affecting the whole globe. With introduction of highly active antiretroviral therapy longevity of HIV patient have increased and they are subjected to high cardiovascular risk as age increases due to various risk factors. Of these dyslipidaemia is one of important risk factor and HIV patients have different degree of deranged lipid profile. Various studies have shown different lipid derangement in these patients but most of them were conducted in urban areas, so this study was conducted to look for lipid profile in HIV patients who are resident of rural areas. Methods: This study was conducted on 66 HIV infected or AIDS cases. Each case was subjected to history taking, through clinical examination and fasting lipid levels. Dyslipidaemia was a classified using NCEP/ATP III guideline. Results: Of total 66 cases, there were 39 male and 27 female with average age of 37 years. Hypercholesterolemia was present in 50% of patients, hypertriglyceridemia in 36.4%. LDL and VLDL were raised in 37.9% and 36.4% respectably while HDL was found below 40 mg/dl in 37.9% of the patients. S. total cholesterol, HDL and LDL was found to have positive correlation while S. TG and VLDL have no significant correlation with CD4 count. Conclusions: Present studies have shown high prevalence of dyslipidaemia in different WHO clinical stage with variable correlation with CD4 count.